(3VeGfGJ JfajP GdbQGQGJ hGdJhUjGJ GdUGOQI Yf BdjI JShjI GdefGRYGJ ai GWGQ efXeI GdJLGQI GdYGdejI (B/ s - (3eMeO Ydi Ydi GdMGL s; (3UdGM GdOjf YGeQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3jJMOO GdgOa ef gPg GdQSGdI ai OQGSI hSGFd JShjI GdefGRYGJ ai efXeI GdJLGQI GdYGdejI HGTcGdgG heQGMdgG GdeNJdaI(B: (3Ke GdfXQ ai LOhi Jdc GdhSGFd(B: (3hGdJQcjR Ydi Jcjja GdbQGQGJ hGdJhUjGJ GdUGOQI YfgG(B: (3Ke GdfXQ a GecGfjI JWHjbgG hJfajPgG(B: (3hGdHMK ai LOhi GdhSGFd GdJi GhQOgG JaGge JShjI GdefGRYGJ ddMK Ydi GdJfajPef NdGd OQGSJgG hJMdjdgG hGdfXQ ai GKGQgG Ydi GWQGa GdfRGY hGdGWQGa GdGNQi(B: (3heOi aGYdjJgG ai JMbjb Pdc GdgOa(B: (3ceG jgOa Gdi GdfXQ HTcd NGU ai YdGbI bQGQGJ efXeI GdJLGQI GdYGdejI hbhGYOgG hGdLRGAGJ GdJi JaQVgG HbQGQGJ hLRGAGJ GdefXeGJ GdOhdjI GdGNQis
(3GWQhMI (B( (3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2009s
(3HHdjhLQGajG(B: (3UaMGJ (B652-719s
Keywords: (3GdbGfhf GdOhdjs; (3efXeI GdJLGQI GdYGdejI s; (3GdfXGe GdJLGQi GdOhdis; (3JShjI GdefGRYGJ GdOhdjI s; (3GdGJaGb GdeJHGOds; (3GdJMcje GdGJaGbjs; (3GdGbJUGO GdbVGFjs; (3LgGR GdGSJFfGa GdOGFes; (3GdeQGLYI GdGSJFfGajIs; (3GdJMcje GdedRes; (3GLQGAGJ GdGeJKGds; (3GdJYhjV GdJLGQjs; (3GdJYhjV GdeGdjs; (3GdJOGHjQ GdeVGOIs; (3JYdjb GdJfGRdGJs; (3GdLRGAGJ GdGbJUGOjI GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs